Introduksi Jeruk Malang sebagai Solusi Konservasi Tanah dan Peningkatan Pendapatan Petani Desa Setren, Kecamatan Slogohimo, Kabupaten Wonogiri - Dwi Priyo Ariyanto; Jaka Suyana; Komariah Komariah; Sumani Sumani; Bardhian Cahyo Aji Gumilang (Universitas Sebelas Maret, 2026)
Introduction of Malang Oranges as a Solution for Soil Conservation and Increasing Farmers' Income in Setren Village, Slogohimo District, Wonogiri Regency. Farmers in Setren Village, Slogohimo District, Wonogiri Regency, located on the slopes of Mount Lawu, face two major challenges: severe land erosion on sloping areas and unstable income due to fluctuations in vegetable prices. This community service activity aimed to introduce Malang citrus cultivation as a dual solution through an adaptive, vegetation-based land conservation approach for sloping land, while simultaneously increasing farmers’ income. The implementation methods included observation of land conditions, extension activities, training, and technical assistance in conservation-based citrus cultivation. The materials emphasized land suitability, which was proven to be highly appropriate (altitude 900–1,400 m above sea level, temperature 18–20°C, Andosol soil), the introduction of three adaptive superior varieties (Siam Madu, Baby Pacitan, and Keprok Batu 55) for sloping land, and cultivation techniques suitable for sloping conditions. Key techniques emphasized included (1) land preparation using terracing systems for erosion mitigation, (2) planting hole preparation with organic manure, (3) selection of certified and healthy seedlings, (4) canopy pruning using a 1–3–9 pattern to maximize productivity, and (5) balanced fertilization. The results of this activity were the transfer of technology and knowledge of modern citrus cultivation to farmers, with a participant satisfaction rate of 58.8%, although strengthening of field-based practice is still required. Malang citrus cultivation is considered potential not only as a more stable source of income, but also as a conservation crop that contributes to erosion control and sustainable land management, and has prospects for development as “pick oranges” agrotourism.